Mekanisme Pertahanan Ego Tokoh Utama Novel “Belok Kiri Langsing” Karya: Achi Tm Tinjauan Psikologi Sastra - Triana, Ade; Kudadiri, Amhar; Marsella, Emma (Universitas Tidar, 2025)
This research aims to analyze the Ego Defense Mechanism of the main character in the novel